A Candide response to Panglossian accusations by Randolph and Dobson: biodiversity buffers disease. Issue 10 (29th May 2013) - OSTFELD, RICHARD S.
SUMMARY: Randolph and Dobson (2012 ) criticize the dilution effect, which describes the negative relationship between biodiversity and infectious disease risk. Unfortunately, their commentary includes distortions, errors of omission, and errors of commission, which are rebutted herein. Contrary to their claims, the dilution effect is not a 'mantra' that asserts that reduced disease risk is a 'universal' outcome of high diversity. Although universality of the dilution effect has not been claimed, and conditions under which diversity can amplify disease risk have been described, the growing literature indicates that the dilution effect is indeed a widespread phenomenon.